2012
DOI: 10.1177/070674371205701003
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Psychopathology in People with Intellectual and other Disabilities

Abstract: Objective: To review the psychosocial, pharmacological, and other treatments of psychopathology in people with intellectual disabilities (IDs), autism, and other developmental disabilities (DDs).Method: Systematic reviews and meta-analyses of psychosocial, pharmacological, and other treatments for people with DDs are reviewed. Results:There is strong evidence for applied behaviour analysis (ABA) and other behavioural treatments of some forms of psychopathology. There is little good evidence to support the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 83 publications
(111 reference statements)
1
19
0
Order By: Relevance
“…To this end, several treatment programs based on operant learning and cognitive models with documented efficacy can be employed such as differential reinforcement strategies (e.g. to reduce inappropriate vocalisations), low level problem solving, assertiveness and goal management training [115][116][117][118]. In certain genetic disorders like Noonan syndrome and Turner syndrome, specific impairments in affective information processing and social interaction can be identified and may be modulated by means of targeted social-cognitive training [119][120][121].…”
Section: Discussionmentioning
confidence: 99%
“…To this end, several treatment programs based on operant learning and cognitive models with documented efficacy can be employed such as differential reinforcement strategies (e.g. to reduce inappropriate vocalisations), low level problem solving, assertiveness and goal management training [115][116][117][118]. In certain genetic disorders like Noonan syndrome and Turner syndrome, specific impairments in affective information processing and social interaction can be identified and may be modulated by means of targeted social-cognitive training [119][120][121].…”
Section: Discussionmentioning
confidence: 99%
“…However, data on the prevalence of mood, anxiety, and psychotic disorders are still not clear because of problems in methodology of the studies (i.e. validity issues), and features of the studied populations [41]. The application of psychiatric diagnostic classification systems originally designed for typically developing individuals to individuals with IDD has frequently been criticized and should be done with caution [34].…”
Section: Psychiatric Diagnosismentioning
confidence: 99%
“…ABA relies on the principles established in learning to modify behavior (Baer et al 1968). Most often used in treating symptoms of autism spectrum disorder, researchers have found that ABA is also effective in treating psychiatric disorders, maladaptive behaviors, self-injurious behaviors, pica, and phobic avoidance (Didden et al 1997(Didden et al , 2006Mafifei-Almodovar and Sturmey 2012;McAdam 2012;Sturmey 2012;Sturmey et al 2012).…”
Section: Behavioral Therapymentioning
confidence: 99%
“…Other areas where further research would be beneficial include reliable diagnosis of psychiatry disorders in person with ID, combined psychopharmacological and psychosocial treatment, and social validation of behavioral changes. First, the reason that research to examine medication to treat comorbid conditions in persons with ID is limited is because of the difficulty of making reliable psychiatric diagnoses in individuals with ID (Sturmey 2012). Thus, as touched on previously, researchers must continue focusing on studying the symptom presentation of comorbid conditions in individuals with ID to support better research.…”
Section: Limitations Of Treatment Researchmentioning
confidence: 99%
See 1 more Smart Citation